PHYSICAL EDUCATION AND SPORTS – THE BASIS OF A HEALTHY LIFESTYLE (International journal of artificial intelligence, 2025)
This article covers the role of physical education and sports in a person's life, the impact on a healthy lifestyle and the need to develop it in modern society. In the formation of a healthy generation, the physiological, psychological and social aspects of physical activity, regular exercise in sports are analyzed. At the same time, recommendations are presented on the role of sports in youth education, the formation of a sports culture and a sedentary lifestyle.